Holistic Proposal To Improve Teaching Performance In Inclusive Education (Journal of Pharmaceutical Negative Results, 2022)
Currently, the problem of inclusive education continues to be one of the most common barriers in the educational system, and one of the fundamental causes would be related to teacher preparation for attention to diversity. In this sense, an investigation was carried out with the objective of designing a holistic proposal aimed at improving teaching performance in inclusive education in a Lambayecan institution. The non-experimental design was used, using the survey technique and a questionnaire, which had a very high reliability and validity with values of 0.82 and 0.97, respectively. The sample consisted of 40 teachers, selected by non-probabilistic sampling under the criteria of homogeneity, accessibility and availability. As a result, it was obtained that 67.5% of teachers are located in the insufficient and sufficient levels regarding the dimensions of understanding, planning, conduction and evaluation. This indicates that a large percentage would require some support to accompany students with special educational needs. In short, it is important to develop strategies based on the particular characteristics and strengths of students that allow them to function independently and safely, both in the academic environment and in society.